Pengaruh Sarana dan Prasarana terhadap Pelayanan kepada Masyarakat di Kantor Kepolisian Sektor (Polsek) Salahutu Kabupaten Maluku Tengah - Natasya Arista; Iriane Sosiawaty Ponto; Julia Theresia Patty (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze the influence of facilities and infrastructure on public service delivery at the Salahutu Sector Police Office, Central Maluku Regency. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to all personnel of the Salahutu Police Sector as respondents. The research instruments were developed based on indicators of facilities and infrastructure and service quality, and the data were analyzed using simple linear regression. The results indicate that facilities and infrastructure have a significant influence on the quality of public services. Adequate and well-managed facilities support work effectiveness and enhance the professionalism of service delivery within the police institution. These findings highlight the importance of strengthening facilities and infrastructure as a strategic effort to improve police service quality, particularly in areas with diverse geographical and social characteristics.